Determination of Zirconium(IV) Based on Flow Injection Analysis with The Xylenol Orange As A Complexing - Waode Rustiah; Sulistyani Sulistyani (Al-Kimia, 2021)
The development of spectrophotometry method based on Flow Injection Analysis (FIA) to determine Zr(IV) in tin ore accompanying mineral has been done using xylenol orange as complexing agent. The complex between Zr(IV) and xylenol orange 0,05% was formed at pH 2 (1:1). The complex formed having maximum absorbance at wavelength 554 nm. The mineral decomposition has been done by fusion method using Na2CO3 and Na2O2 as fluxs for open system and the close system decomposition using HNO3, HClO4 and HF as solvents. FIA-spectrophotometry that has been developed was able to show good analytical performance, with precision of %KV not more than 5% at concentration level mg/L, was 3,98%, with sensitivity was 2,79 ppm and the detection limits of calculated (S/N = 3) was 0,21 ppm. This method has been aplicated for analyzing Zr(IV) in zircon mineral sample with analysis result 20,26% of ZrO2 and recovery percentage was 100,7%.